Analysis of The Differences Between Warning and Prohibition Expressions in Indonesia and English in English Textbooks - Agung Ahdiansyah; Alwi Nalfiyah (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
Various ways of disclosing or delivering communication in the form of expressing warnings and expressing prohibitions or delivering information this study aims to determine the differences between warning and prohibition expressions in Indonesia and English and the forms of these expressions. This research process used qualitative research methods and literature studies. To collect the data, this research employed textual observation. Meanwhile, to analyze the data this study employed cultural analysis. The result can be seen that expressing warnings and expressing prohibitions declared in Indonesia and abroad are not much different, both in terms of expression and form, such as no smoking, no food and drink in this area, etc.